'Prolixity is a Woman's Crime': Assessing Long-windedness in Seventeenth-century Women's Writing. Issue 1 (1st June 2021) - Start, Eleanor
Abstract : Gendered critiques of language have long been a feature of written discourse, and perhaps in no era more tellingly than the seventeenth century, a period in which female writers came to the fore and told their stories for the very first time. Through an examination of This is a Short Relation of Some of the Cruel Sufferings (For the Truth's Sake) of Katherine Evans and Sarah Cheevers (1662) and Mary Trye's 1675 treatise Medicatrix, this essay explores the assumption that women's writing is long-winded. Assessing their religious, medical and even proto-feminist messages, the essay analyses rhetorical devices and their effect, and how context heavily influenced the length of each publication. More than an historical record of their struggle, these texts articulate the voices of women previously unheard. While the two texts would seem at odds, the former concerning Quakerism and the latter medicine, they prove comparable in all their contrasts, revealing how women during this period of history displayed extraordinary innovation in their writing.